DESIGN AND BUILD A WEBSITE-BASED FOREIGNER SERVICE APPLICATION APPLICATION AT THE CLASS 1 IMMIGRATION OFFICE SPECIFICALLY FOR NON-TPI WEST JAKARTA - G.B Hertantyo; I.A Prabadhi; G.S Paramitha (Polteknik Imigrasi, 2022)
The use of information technology has now been widely applied in the process of immigration services and supervision carried out by the Directorate General of Immigration. One of them is return of immigration documents and transferring foreigner data using a Google form. However, in its implementation there are still some problems. This study aims to determine the current business process for document return services and foreigner data mutations at West Jakarta Immigration Office and to provide an overview of designing a web-based application for immigration services for foreigner. The design of this application uses the Waterfall Model System Development Life Cycle (SDLC) method. The results of this study are a website-based application prototype for foreign citizen services with various features provided such as checking application status, information on requirements for submitting requests for return of immigration documents and mutation of foreigner data, submission of ERP applications, submission of EPO applications, submission of transfer requests address, and submission of a passport mutation application which can later be used as a reference to be applied to immigration document return services and foreigner data mutations at the Special Class 1 Immigration Office for non-TPI West Jakarta.